INBRX-120, a CD8α-targeted detuned IL-2 that selectively expands and activates tumoricidal effector cells for safe and durable in vivo responses. Issue 1 (18th January 2023) - Sulzmaier, Florian J; Kern, Nadja; Ahn, Sae Jeong; Polovina, Anya; Ho, Jason; Hussain, Abrahim; Cyprus, Garrett; Macedo, Chelsie; Pandit, Rajay; Crago, William; Rowell, Emily; Timmer, John C; et al.
Abstract : Background: As a major driver of lymphocyte proliferation and activation interleukin 2 (IL-2) is a crucial mediator for antitumor responses. Despite promising activity in a subset of patients, wider therapeutic utility of IL-2 (aldesleukin) has been hampered by severe dose-limiting toxicities, the expansion of immunosuppressive regulatory T cells and a poor pharmacokinetic (PK) profile. Recent engineering efforts, including non-α IL-2 variants, have lowered the toxicity profile, but have yet to induce meaningful antitumor activity in a wider patient population. Methods: We engineered INBRX-120, a CD8α-targeted Cisleukin™ molecule consisting of an affinity tuned IL-2 (IL2-x) connected to two high affinity CD8α-specific single domain antibodies via an effector-silenced Fc domain. To show that this large affinity differential enables directed IL-2 cis-signaling exclusively on CD8α-expressing tumoricidal effector cell populations, INBRX-120 effects on target cell expansion, activation and antitumor activity were tested in vitro. In vivo antitumor efficacy was evaluated in syngeneic mouse models alone or in combination with programmed cell death protein-1 (PD-1) blockade. Preclinical safety, as well as pharmacodynamic (PD) and PK profiling was carried out in non-human primates. Results: INBRX-120 effectively expanded and enhanced the cytotoxic capacity of CD8 T cells and natural killer cells towards tumor cells without affecting regulatory T cells in vitro and in vivo. In syngeneic mouse models, INBRX-120 surrogate showed safe, potent, and durable antitumor efficacy alone and in combination with PD-1 blockade. In non-human primates, INBRX-120 expanded and activated CD8α-expressing effector cells, showed a favorable PK profile, and was well tolerated up to a dose of 1 mg/kg. Conclusions: Through its unique cis-signaling activity on CD8α-expressing effector cells, INBRX-120 overcomes the major limitations of IL-2-based therapy and effectively harnesses IL-2's potent intrinsic antitumor activity. This novel therapeutic strategy promises safer clinical activity that could induce meaningful antitumor efficacy in a wider set of patients with various cancer indications.